Probabilistic weather forecasting using Bayesian model averaging: The case of SAGCOT regions - Joel, Emmanuel (Mzumbe University, 2023)
A dissertation submitted in partial/ fulfillment of requirements for award of the Degree of Master of Science in Applied Statistics of Mzumbe University